Combined capacitive and electrochemical charge storage mechanism in high-performance graphene-based lithium-ion batteries. (March 2022) - Scaravonati, Silvio; Sidoli, Michele; Magnani, Giacomo; Morenghi, Alberto; Canova, Marcello; Kim, Jung-Hyun; Riccò, Mauro; Pontiroli, Daniele
Abstract: Improvements in lithium (Li)-ion battery technology can be achieved by developing novel, high-performance electrode materials. Graphene appears to be a good candidate as an anode material for Li-ion batteries thanks to the similarity with graphite, the good electrical conductivity, the ability to achieve fast charge and discharge cycles, and the higher capability to host Li ions. Our previous studies demonstrated the capability of intercalating Li in graphene-based electrodes with a high specific capacity of 500 mA h/g at C/5 current. In this study, graphene, synthesized through scalable thermal exfoliation of graphite oxide, and hydrogenated graphene are used to assemble optimized Li-ion half-cells, which are systematically characterized by means of electrochemical measurements. Hydrogenated graphene boasts an impressive reversible specific capacity with fast charge/discharge capabilities, exceeding 370 mA h/g even at 25 C rate. Diffusion mechanisms of Li are characterized at different states of intercalation by means of electrochemical impedance spectroscopy. In addition, a novel combined electrostatic and electrochemical charge storage mechanism of Li ions in graphene-based electrodes is proposed, based on three-electrode cyclic voltammetry investigation. Furthermore, graphene and hydrogenated graphene anodes are paired with commercial cathode materials to study the feasibility of their application to full cells. Graphical abstract: Image 1 Highlights: Graphene-based half-cells were realized. Graphene was hydrogenated to improve electrochemical performances. Diffusion of lithium in graphene and hydrogenated graphene was investigated. A combined electrochemical-electrostatic charge storage mechanism was proposed. Full-cells with graphene and hydrogenated graphene anodes were assembled.